Comparison of the patients undergoing total knee arthroplasty with and without drain in terms of functional outcome, hemoglobin drop and infection rate - K. V., Shamseer; T., Pradeep Kumar; G. M., Shameem; Khan , Prince Shanavas (International Journal of Research in Orthopaedics, 2025)
Background: There is still no consensus about use of post-op drain in TKA. We compared postoperative outcomes of TKA with drain and without drain in terms of hemoglobin drop, functional outcome and infection. Methods: An observational cohort study was conducted at a tertiary hospital between March 2023, and March 2024. Men and women with primary OA knee and age more than 40 years were included. Patients on antiplatelets, with acute and active infection, revision TKA, malignancy were excluded. Results: 90 patients were included age range 50-80 years. Males to female ratio was 74.4:25.6. Of 90 patients, 45 (50%) received a drain. The drain group had greater hemoglobin drops. There was no statistically significant difference in functional outcome by KOOS score and WOMAC score in both groups. There was no significant difference in occurrence of infection in both groups. Conclusions: This comparative study aimed to assess the outcomes of total knee arthroplasty (TKA) with and without drain insertion, focusing on hemoglobin drop, functional outcomes measured by (KOOS) and (WOMAC) scores, and infection rates. In conclusion, my study supports reconsidering routine drain use in TKA procedures, as omitting drains was associated with a notable reduction in hemoglobin drop without compromising functional outcomes or increasing infection risks. Surgeons should carefully weigh the potential benefits of reduced blood loss against the need for drainage and associated risks, considering individual patient factors and surgical circumstances.